Sportowe pasje kobiet. Przyczynek do jakościowych badań nad zawartością treści w prasie regionalnej i lokalnej Wielkopolski oraz jej pogranicza - Jurga-Wosik, Ewa (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
The transformation of the political communication models in Venezuela and other Latin American states is related to the evolving political culture in this region, together with a bold use of media communication approached both as a means and a goal. Video-politics, defined as a process of the mediatization of the constructs of political reality, is becoming a key notion for the citizens and voters there. Using the public means of social communication Hugo Chávez has made the Aló, Presidente show an arena of political decision-making and a space focused on political personalism. An analysis of selected elements of the show provides detailed information on the rhetorical tools and other mechanisms of exerting influence applied by Hugo Chávez. On a macro-scale the media strategies applied in the show turn out to be instruments of consolidating the image of executive power in Venezuela.
Political Communication in Latin America on the example of the activity of Venezuela President Hugo Chávez